1999
DOI: 10.1136/pgmj.75.886.463
|View full text |Cite
|
Sign up to set email alerts
|

Do Indo-Asians have smaller coronary arteries?

Abstract: SummaryThere is a widespread belief that coronary arteries are smaller in Indo-Asians. The aim of the present study was to compare the size of atheroma-free proximal and distal epicardial coronary arteries of Indo-Asians and Caucasians. We analysed normal coronary angiograms from 77 Caucasians and 39 Indo-Asians. The two groups were comparable for dominance of the coronary arteries. Indo-Asian patients had generally smaller coronary arteries, with a statistically significant diVerence in the mean diameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 11 publications
4
67
0
Order By: Relevance
“…We found larger calibers in LCA than RCA. These findings are consistent with angiographic and post-morten measurements [19][20][21][22][23][24] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We found larger calibers in LCA than RCA. These findings are consistent with angiographic and post-morten measurements [19][20][21][22][23][24] .…”
Section: Discussionsupporting
confidence: 80%
“…Curiously, Lip et al [23] found in indoasian people a narrower caliber of 2.98 mm. Equally with our results, Dodge et al [21] and Kaimkhani et al [24], found a correlation between coronary dominance and caliber, being higher in hearts with right dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that age, body weight gender, genetics, and ethnicity play a role in this difference. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this study, we preferred using a tabular format to compare our study with earlier studies that employed a similar working methodology ( Table 3). Our study results were comparable to those of the studies conducted in the Iraqi population.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Lumen diameter of normal human coronary arteries and several factors affecting their lumen diameters have previously been studied in different countries on different populations. [5][6][7][8][9][10] To the best of our knowledge, there is no study with international recognition regarding normal Angiographic analysis of normal coronary artery lumen diameter in a Turkish population* coronary artery diameters in Turkish population. The aim of this study was to measure the coronary artery diameters of the individuals with normal coronary arteries on angiographic images, to assess the association among the different diameter values as well as the effect of age and the gender on the diameters, and finally compare our results with those from other populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation